2019
DOI: 10.1039/c9qi00765b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical properties of chromium oxyfluoride CrO2−xFx with 0 ≤ x ≤ 0.3

Abstract: To overcome the limitations of graphite as a negative electrode material for lithium-ion batteries (LIBs), transition metal oxyfluorides are under active development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…properties. The reason to select the HP/HT method was that the high concentration of F − ions and the stabilization of the rock-salt structure are achievable under HP/HT conditions (12 GPa and ~1000 °C) as reported in CrO 2−p F p (p ≤ 0.3) 14 and Li-Co-Mn oxides 15 , respectively, and the high crystallinity of the compounds is maintained. We successfully synthesized highcrystallinity Li 3 VO 3 F and Li 4 WO 4 F and revealed that their electrochemical reactions involving a decomposition reaction.…”
Section: Syntheses Of LImentioning
confidence: 99%
See 2 more Smart Citations
“…properties. The reason to select the HP/HT method was that the high concentration of F − ions and the stabilization of the rock-salt structure are achievable under HP/HT conditions (12 GPa and ~1000 °C) as reported in CrO 2−p F p (p ≤ 0.3) 14 and Li-Co-Mn oxides 15 , respectively, and the high crystallinity of the compounds is maintained. We successfully synthesized highcrystallinity Li 3 VO 3 F and Li 4 WO 4 F and revealed that their electrochemical reactions involving a decomposition reaction.…”
Section: Syntheses Of LImentioning
confidence: 99%
“…Li x MO 1+x−y F y (M = Fe, Mn, V, Nb, Mo, and W) was synthesized using the HP/HT method with a Walker-type apparatus installed at Osaka Prefecture University. 14,15 1000 °C for 30 min. The procedure has been described in further detail elsewhere.…”
Section: Sample Preparation and Phase Identificationmentioning
confidence: 99%
See 1 more Smart Citation